2021
DOI: 10.1186/s12245-021-00333-0
|View full text |Cite
|
Sign up to set email alerts
|

Hiccups and psychosis: two atypical presentations of COVID-19

Abstract: The WHO defines a possible case of COVID-19 as a person experiencing fever, cough, shortness of breath, and neurological signs including anosmia, ageusia, or dysgeusia. However, experiences from hospitals all over the world have shown that presentations vary widely. Some atypical presentations include cardiac, gastrointestinal, neurological, and cutaneous and while some are driven by the inflammatory response, others are a consequence of the hypercoagulable state. In our emergency department in a private hospi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 19 publications
0
18
0
2
Order By: Relevance
“…Finally, 18 articles did not include individual level data and 7 articles were available as abstracts only. A total of 40 articles met inclusion criteria, comprising 48 individual patients from 17 countries ( Table 1 ) [ [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] ]. All but a single study [ 54 ] were in English and 20 (42%) cases were reported in the United States, where the largest proportion of these cases were documented.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, 18 articles did not include individual level data and 7 articles were available as abstracts only. A total of 40 articles met inclusion criteria, comprising 48 individual patients from 17 countries ( Table 1 ) [ [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] ]. All but a single study [ 54 ] were in English and 20 (42%) cases were reported in the United States, where the largest proportion of these cases were documented.…”
Section: Resultsmentioning
confidence: 99%
“… Reported DX: acute psychosis or transient psychotic disorders DSM-5 Dx: Brief psychotic disorder Recent mechanical ventilation, treatment with dexamethasone and HCQ. Alvarez-Cisneros et al, 2021 [ 27 ] 43, M, MX Tachylalia, disorganized ideas, restlessness, delusions of grandeur, emotional lability, and aggression towards his mother presenting 3 days after father diagnosed with COVID-19. No symptoms A history of hetero-aggressive episodes which usually resolved over 48 h. None + SARS-CoV-2 PCR.…”
Section: Resultsmentioning
confidence: 99%
“…We noticed that there were quite a few patients who developed hiccups. To date, 10 short cases have been reported on this topic [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] . We witnessed five cases in succession; therefore, we assume that hiccups might be a specific symptom of COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…SARS-CoV-2 has a neurogenic tropism recognized, the main mechanism known states that after binding to the receptors of the angiotensin converting enzyme II (ACE2) in the nasal epithelium, it invades the olfactory nerve and the bulb, progressing, to later invade the respiratory centers of the brainstem. To date, we have found in the literature six cases of persistent singultus in men positive to SARS-CoV-2 infection of different ethnic origin in the range of 48-62 years (table I), [1][2][3][4][5][6] three of them Mexican with comorbidity.…”
mentioning
confidence: 99%
“…Armando Totomoch-Serra, PhD, MD, (1,2) totomoch@gmail.com Concepción B Ibarra-Miramon, MD, (3) Carlos Manterola, MD, PhD. (1,2) (…”
mentioning
confidence: 99%